Discontinuous dynamics in North Sea cod Gadus morhua caused by ecosystem change - Blocker A. M.; Sguotti C.; Mollmann C. (Marine Ecology Progress Series, 2023)
Marine ecosystems worldwide experience abrupt changes and regime shifts in structure and functioning due to the interacting effects of multiple stressors. North Sea cod Gadus morhua is a key example of a species being strongly overexploited for decades, causing an abrupt stock decrease below scientifically advised sustainable levels. Despite reductions in fishing pressure in recent years, populations of North Sea cod have not yet recovered. Why recovery is hindered and especially how ecosystem dynamics interacted with fishing to create a stable low cod stock is an open question. Here, we sequentially apply change point and principle component analyses as well as stochastic cusp modelling to a long-term time series (1963−2018) to show that North Sea cod recovery is limited due to an interaction of fishing pressure, internal stock dynamics and external environmental changes. We found that cod biomass experienced nonlinear, discontinuous dynamics, given the interaction of fishing pressure and climate change-induced increases in temperatures, wind magnitude and the North Atlantic Oscillation. Our results further demonstrate discontinuity in cod biomass due to low recruitment caused by a discontinuous relationship between stock biomass and environmental changes characterized by climate and zooplankton variables. Our study indicates that climate-induced changes in the environment have trapped North Sea cod in a depleted state, limiting the probability that the population will regain its role as a main target species for fisheries. Hence, we highlight the importance of incorporating discontinuous dynamics in fisheries management approaches to achieve sustainable exploitation levels and to identify thresholds of drivers to favour policies to prevent regime shifts.